Desindustrialização no Brasil e aspectos regionais : uma análise com enfoque no Nordeste - Vasconcelos, Helma Monteiro Viana (2017)
This dissertation analyzes the process of the Brazilian deindustrialization economy expanding the observation´s profile to the regions of the country, especially in the Northeast. For this, it exposes the world´s productive restructure with the growth trend of the services sector in aggregate production compared to other economic sectors and how this process happens in a different way in developed countries and in developing countries as well. Analyzes yet Brazil´s deindustrialization from the dynamics of the sector over the years, making it clear that this process happens after the adoption of liberalization measures in the 1990s, once that at that time most of the intensive nacional tecnology industries sectors, hadn´t reached a sufficiently mature competitive level, except for a few sectors like, for example, the aerospace and aeronautics sector, that recorded market gains over the years; on the opposite, in other sectors wasn´t possible to avoid the growth of the use of imported inputs in production, and also the growth of sales abroad of non-industrial intensive products in natural resources, factors that cooperate for the industry to lose prematurely Its role in the economy of the country. Finally, on the regional aspects of the deindustrialization, the paper addresses the "regional question" which the northeast was included, mentioning the industrial concentration and deconcentration that took place in the country and finally the analysis show that most regions confirm the nacional´s employment process of deindustrialization; and talking about the production of available data between 2002 and 2014, also suggest the same, the exception is the Midwest that showed a growth of employment levels and in the transformation industry production. Even so, there are in all regions international insertion, through non-industrialized products, mostly in the North, Southeast and South, as well as the breakdown of production chains, except for the North and Midwest regions. Specifically in the northeastern region was verified a deindustrialization that was related to the employment between 1985 and 2015, as well as the loss of the degree of industrialization from 2010 to 2014 which in turn, the region's external sales have been based on low-tech or non-industrialized products, following the national trend of reprimarization.